Derivation of a comprehensive semi-empirical proton RBE model from published experimental cell survival data collected in the PIDE database - Jin, Jian-Yue; Yuan, Jiankui; Qin, Xiaohang; Li, Yinghui; Yan, Huagang; Oleinick, Nancy L.; Yao, Min; Pan, Quintin; Kong, Feng-Ming (Spring); Machtay, Mitchell (Frontiers in Oncology, 2024)
We aimed to develop a comprehensive proton relative biological effectiveness (RBE) model based on accumulated cell survival data in the literature. Our approach includes four major components: (1) Eligible cell survival data with various linear energy transfers (LETs) in the Particle Irradiation Data Ensemble (PIDE) database (72 datasets in four cell lines); (2) a cell survival model based on Poisson equation, with α and β defined as the ability to generate and repair damage, respectively, to replace the classic linear–quadratic model for fitting the cell survival data; (3) hypothetical linear relations of α and β on LET, or α(LET)αx=αα+bα ∗ LET and β(LET)βx=αβ−bβ ∗ LET; and (4) a multi-curve fitting (MCF) approach to fit all cell survival data into the survival model and derive the aα, bα, aβ, and bβ values for each cell line. Dependences of these parameters on cell type were thus determined and finally a comprehensive RBE model was derived. MCF showed that (aα, bα, aβ, bβ) = (1.09, 0.0010, 0.96, 0.033), (1.10, 0.0015, 1.03, 0.023), (1.12, 0.0025, 0.99, 0.0085), and (1.17, 0.0025, 0.99, 0.013) for the four cell lines, respectively. Thus, aα = 1.12 ± 0.04, bα = 0.0019 ± 0.0008, aβ = 0.99 ± 0.03, and bβ = 0.013 ∗ αx, and approximately α∼1.12∗αx and β=(0.99−0.013∗αx∗LET)∗βx. Consequently, a relatively reliable and comprehensive RBE model with dependence on LET, αx, βx, and dose per fraction was finally derived for potential clinical application.